Strategic Management of Qur'anic Recitation Teaching Among Primary School Teachers in Malaysia - Mohd Aderi Che Noh; Hasnan Kasan; Yusni Mohamad Yusak; Sri Andayani Mahdi Yusuf (Al-Hayat Al-Istiqomah Foundation, 2019)
This study is related to the perception of Islamic Education teachers on their teaching practices in the Qur'an recitation skills due to the national primary schools under the administration of Education Ministry. A total of 120 Islamic Education teachers were involved as respondents in this study. They were randomly selected from ten districts in Selangor. Data were collected through a set of questionnaires consisting of 32 items. Descriptive statistics consisted of frequency, percentage and mean were used to report the findings. Findings showed that the average means of all four components in teaching practices were high. The component of lesson induction showed mean=4.03, the component of lesson expansion showed mean=4.18, the component of lesson closure showed mean=4.03 and the component of teaching aids showed mean=3.77. In conclusion, teachers should ensure a continuous improvement in their teaching practices especially in Quran recitation skills.Penelitian ini terkait dengan persepsi guru Pendidikan Islam tentang praktik mengajar mereka dalam keterampilan membaca Al-Qur'an karena sekolah dasar nasional di bawah administrasi Departemen Pendidikan. Sebanyak 120 guru Pendidikan Agama Islam dilibatkan sebagai responden dalam penelitian ini. Mereka dipilih secara acak dari sepuluh distrik di Selangor. Data dikumpulkan melalui seperangkat kuesioner yang terdiri dari 32 item. Statistik deskriptif terdiri dari frekuensi, persentase dan rata-rata digunakan untuk melaporkan temuan. Temuan menunjukkan bahwa rata-rata rata-rata keempat komponen dalam praktik mengajar tinggi. Komponen induksi pelajaran menunjukkan rata-rata = 4.03, komponen ekspansi pelajaran menunjukkan rata-rata = 4.18, komponen penutupan pelajaran menunjukkan rata-rata = 4.03 dan komponen alat bantu mengajar menunjukkan rata-rata = 3.77. Sebagai kesimpulan, guru harus memastikan peningkatan berkelanjutan dalam praktik pengajaran mereka terutama dalam keterampilan membaca Al-Quran.